Ethanol challenge in non-alcoholic patients with schistosomiasis. Issue 3 (March 1993) - Martins, R D; Borges, D R
Abstract : AIMS: To evaluate serum gamma glutamyltransferase (GGT) activity in a group of non-alcoholic patients with the hepatointestinal form of schistosomiasis; and the response of both GGT and alkaline phosphatase to an ethanol challenge in two subgroups of patients with different baseline serum concentrations of GGT. METHODS: Seventy six non-alcoholic, non-smoking hepatitis B virus (HBV) negative men with normal body mass index, who denied blood product transfusion or use of medication, were studied (30 healthy volunteers (control group) and 46 patients with the hepatointestinal form of schistosomiasis). GGT activities were determined in all subjects and the ethanol test (measurement of GGT and alkaline phosphatase (ALP) before and 24 hours after the ingestion of 1 g/kg of ethanol) was performed in 14 patients (7 with GGT below 25 IU/l and seven with GGT above 25 IU/l). The ethanol serum concentrations were determined in the samples collected one hour after ingestion of the solution in four patients with schistosomiasis. RESULTS: The mean serum ethanol concentration one hour after the ingestion was 0.7 g/l and all patients were clinically intoxicated. GGT was below 25 IU/l in all 30 volunteers and in 33 of the patients with schistosomiasis. In 13 patients the GGT varied from 28 to 140 IU/l. The two enzymes GGT and ALP determined in the 14 patients submitted to the test were positively correlated in the baseline samples (r = 0.8130) as well as in the samples obtained 24 hours after stimulation (r = 0.7921). Neither the plasma activity of GGT nor the GGT:ALP ratio was affected by the ethanol challenge. CONCLUSIONS: These results suggest that the mechanisms for the increase of GGT serum activity in schistosomiasis and in alcoholism differ. In the latter, microsomal induction increases GGT serum activity, while alterations in the biliary tree may be responsible for the increase observed in patients with schistosomiasis.